Model Bisnis Ekowisata di Taman Nasional Laut Bunaken dengan Pendekatan Business Model Canvas - Mawardi Ps Bagindo; Bunasor Sanim; Teguh Saptono (Institut Pertanian Bogor, 2016)
The role of tourism sector increasingly important in line with the development of Indonesian economic structure leading to services sector. Business modelling approach is one of the critical factor to the success of an organization. Bunaken National Marine Park in North Celebes is a representative of the tropical water ecosystem in Indonesia that consists of mangrove, seagrass, coral reefs and coastal. The objective of this research were to identify the business modelling of Bunaken and to analyze its improvements using descriptive-qualitative method. Business modelling method were analyzed by business model canvas 9 building block. Increasing of the value proposition, costumer segment, costumer relationship would be affected to revenue stream organization. Supporting the value proposition needed key activities, key resources and key partnership. The management of Bunaken should have the appropriate human resources to apply this modelling.